Comparison of adherence, persistence, and clinical outcome of generic and brand-name statin users: A retrospective cohort study using the Japanese claims database. Issue 5 (May 2021) - Gao, Jingwei; Seki, Tomotsugu; Kawakami, Koji
Highlights: Generic statin users have better adherence and persistence to treatment. Clinical outcomes were similar for generic and brand-name statin users. Findings of this study strengthen confidence in generic substitution policies. Abstract: Background: Non-adherence to statin treatment results in an increased risk of cardiovascular events and all-cause mortality. This study compared adherence, persistence, and clinical outcomes of patients who initiated brand-name and generic statins in the Japanese population. Methods: The retrospective cohort study included adult patients who initiated statins between 2014 and 2016. Primary adherence was measured as the proportion of days covered (PDC) within 1 year. Persistence was assessed using the proportion of non-persistent users. Any major adverse cardiac and cerebrovascular event (MACCE) was assessed as a clinical outcome. Propensity score matching was performed to adjust for confounding factors. Results: Among 47, 770 patients who met inclusion criteria in the study, 32, 130 (67.3%) initiated generic statins. The median age of the patients was 53 (interquartile range: 46-59) years and 60.2% were male. A higher proportion of patients with PDC ≥80% [60.2% vs. 57.1%; odds ratio, 1.14; 95% confidence interval (CI), 1.09–1.19; p <0.001] and a higher PDC value (median, 90.2% vs. 87.9%; difference, 2.3%; p <0.001) were observed in the generic group. Similarly, fewer patients discontinued statins in the generic group [24.2% vs. 27.7%; hazard ratio (HR), 0.91; 95% CI, 0.87–0.95; p <0.001]. Differences in MACCE occurrence were not significant between the groups (4.3% vs. 4.2%; HR, 1.04; 95% CI, 0.93–1.17; p =0.99). Conclusions: Adherence and persistence were higher among generic statin recipients; nevertheless, no significant differences in clinical outcomes were noted between the two groups, suggesting that generic medication did not impair treatment benefits and may improve patient adherence.